Ethical Code of Judges of the Wrestling Federation of the Islamic Republic of Iran - Morteza Zoormand Safanjani; Hossein Poursoltani Zarandi; Morteza Rezaei Sufi (Islamic Azad university, Isfahan Branch, 2022)
Objective: The present study was conducted with the aim of developing a code of ethics for judges of the Wrestling Federation of the Islamic Republic of Iran.Methodology: According to the purpose, this research is one of the applied researches which is a survey in terms of implementation method. The study population of the present study was all the judges of the Wrestling Federation of the Islamic Republic of Iran in an unknown number, which due to inconsistency in summarizing the statistics of the total number of judges, no accurate information was found. In order to determine the sample, the number of subjects according to the adequacy of the sample size in the measurement model, which according to Hir (2012) was determined to be at least 200 people, 258 people were identified as members of the research sample. The research measurement tool is a researcher-made ethical questionnaire by Likert method (five options). This 48-item questionnaire was designed in the form of 9 main components of rule of law, respect, ranking, professional attitude, honesty and trustworthiness, justice, responsibility, related to the heroic character. Exploratory and confirmatory factor analysis for construct validity are used to identify questions and components, one-sample t-test is used to examine the status of questions, components and the concept of ethical code, and Friedman test is used to prioritize questions and components.Results: The results of statistical tests showed that the average components of the judges's moral system in the ship in the sample is above 3, so in the sample has a desirable level and it can be said that the components of the judges's moral system is at the desired level. Also, according to Wilcoxon test for the difference of components with each other to follow the rankings, it was found that there is no difference between honesty, trustworthiness with dignity and respect with heroism and also respect with dignity, while a significant difference was observed between all subsequent components.Conclusion: It seems that the ethics and moral virtues among the judges are not due to their credibility and career advancement, but these components are mixed with their spirit and character and after a lifetime in the world of wrestling and gaining different experiences. It has become part of the morale and ethics of these judges.